Defining trustworthiness in service oriented environment - Hussain, Farookh Khadeer; Chang, Elizabeth; Dillon, Tharam S. (IEEE Computer Society Press, 2006)
In the existing literature we note that there has been no effort in proposing a definition of trustworthiness. In this paper, we propose a definition of trustworthiness with focus on service oriented environments. In addition, we propose and discuss in detail the various factors which can affect the trustworthiness assigned by the trusting agent to the trusted agent.